2014
DOI: 10.1152/ajplung.00265.2013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced lysis and accelerated establishment of viscoelastic properties of fibrin clots are associated with pulmonary embolism

Abstract: The factors that contribute to pulmonary embolism (PE), a potentially fatal complication of deep vein thrombosis (DVT), remain poorly understood. Whereas fibrin clot structure and functional properties have been implicated in the pathology of venous thromboembolism and the risk for cardiovascular complications, their significance in PE remains uncertain. Therefore, we systematically compared and quantified clot formation and lysis time, plasminogen levels, viscoelastic properties, activated factor XIII cross-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 27 publications
0
37
1
Order By: Relevance
“…These findings indicating a similar pattern of changes in fibrin characteristics as a predictor of recurrent PE and DVT 10 are surprising. Martinez et al 11 reported that clots made from plasma of patients with acute isolated PE were characterized by faster CLT and lower fiber density when compared with DVT alone. On the contrary, perfusion defects after PE and chronic thromboembolic pulmonary hypertension have been shown to be associated with impaired fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicating a similar pattern of changes in fibrin characteristics as a predictor of recurrent PE and DVT 10 are surprising. Martinez et al 11 reported that clots made from plasma of patients with acute isolated PE were characterized by faster CLT and lower fiber density when compared with DVT alone. On the contrary, perfusion defects after PE and chronic thromboembolic pulmonary hypertension have been shown to be associated with impaired fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Clots derived from the blood of subjects with pulmonary embolism showed accelerated establishment of viscoelastic properties compared to healthy donors (Martinez et al 2014). In addition, the stiffness of clots formed from the blood of patients who have had heart attacks at an early age is 50 % greater than that of controls (Collet et al 2006).…”
Section: 5 Fibrin Mechanical Properties and Their Structural Originsmentioning
confidence: 99%
“…Based on viscoelastic properties of incipient blood clots, a new biomarker of healthy, bleeding or prothrombotic clot microstructure was proposed, named the fractal dimension, which has been shown to have clinically important correlations [31-33]. Clots derived from the blood of subjects with pulmonary embolism showed accelerated establishment of viscoelastic properties compared to healthy donors [34]. Studies have shown that the stiffness of clots formed from the blood of patients who have had heart attacks at an early age is 50% greater than that of controls, indicating that these clots are abnormal [35].…”
Section: Viscoelastic Properties Of Fibrin (Fibrin Rheology)mentioning
confidence: 99%